Strategic Development of Campus-Based Social Entrepreneurship and Islamic Philanthropy: A Business Model Canvas (BMC) Perspective - Dicky Chandra; Nuryadi Wijiharjono; Puspo Dewi Dirgantari; Agus Rahayu; Lili Adi Wibowo; Nur Hadiyazid Rachman (Journal of Islamic Economics and Business, 2025)
Universities remain underutilized in addressing pressing issues of poverty, unemployment, and inequality. This study aims to develop a structured framework that integrates social entrepreneurship and Islamic philanthropy into academic moral responsibility. Using a qualitative method, the research combines Critical Literature Review (CLR) and Soft Systems Methodology (SSM) through a case study of the Islamic Philanthropreneurship Lab (LKSFI). Findings reveal two key outcomes: (1) a theoretical-philosophical foundation for embedding social entrepreneurship and philanthropy in higher education, and (2) a redesigned Business Model Canvas adapted for university-based philanthropic ventures. This framework offers a strategic tool to enhance universities' social missions and institutional alignment.